The Silent Past of the Buitenkampers and Their Lost Identity - Larder, Frances Henriette Emelia (Curtin University, 2018)
Combining an exhibition and a written work, this study reveals the experiences of Buitenkamper children from the Netherlands East Indies, not incarcerated during the Japanese Occupation (1942-1945), who also endured the violent start of the Indonesian Revolution for Independence (1945-1946). Many were subjected twice or thrice to migration before resettling in Australia. Their stories are analysed for the first time revealing the impacts of war, revolution and diaspora on sense of place, identity and belonging.